Study of acyl migration during enzymatic interesterification of liquid and fully hydrogenated soybean oil - Pacheco, Consuelo (2015)
Lipase-catalyzed interesterification has emerged as an attractive process to obtain plastic fats because of its numerous advantages compared to the chemical reaction. The use of sn-1,3 specific lipases adds an even more interesting feature to this process, which is related to the possibility of maintaining the sn-2 fatty acid composition of natural substrates unaltered. The pursuit of this characteristic in interesterified products by sn-1,3 specific lipases could be threatened by a chemical reaction, the acyl migration whithin mono- and diacylglycerols. The aim of this study was to evaluate the occurrence of this undesired reaction in a soybean oil:fully hydrogenated soybean oil enzymatic interesterified blend. Once acyl migration was confirmed to occur, the influence of different reaction parameters -namely enzyme type and concentration, substrate ratio, and addition of hexane and temperature effect- was studied. Lipozyme TL IM demonstrated an enhancer acyl migration effect compared to Lipozyme RM IM, effect that was hypothesized to be correlated with the immobilization support material of the former (silica gel). Acyl migration was also promoted by the increase of biocatalyst concentration in reaction media. On the contrary, the presence of hexane, together with a decrease in temperature reaction, reduced its occurrence. A temperature effect analysis performed in solvent reaction media demonstrated its promoter effect on acyl migration.